Long Term Outcome of Postoperative Atrial Fibrillation After Cardiac Surgery—A Propensity Score-Matched Cohort Analysis - Hsu, Jung-Chi; Huang, Chen-Yu; Chuang, Shu-Lin; Yu, Hsu-Yu; Chen, Yih-Sharng; Wang, Chih-Hsien; Lin, Lian-Yu (Frontiers in Cardiovascular Medicine, 2021)
Background Postoperative atrial fibrillation (POAF) results in a longer hospital stay and excess mortality. However, whether POAF would increase stroke rate has been debated for years. When and how long should anticoagulation be used to prevent stroke are unknown. In the study, we planned to investigate the clinical demographics and long-term outcomes of POAF after cardiac surgery in a single-center cohort. Methods The cohort study used a database from National Taiwan University Hospital, a single tertiary medical center in Taiwan, between 2007 and 2017, to identify patients with prior normal sinus rhythm developing POAF after cardiac surgery. Patients without POAF after cardiac surgery were used as controls. Propensity score matching with 1:1 ratio and Cox regression models were employed to estimate the risk of transient ischemic accident (TIA) or ischemic stroke. Results From 2007 to 2017, a total of 8374 patients received open-heart surgery, in which 1585 patients with history of AF were excluded. The overall incidence of TIA/ischemic stroke was 3.9% in a median 9.2-years of follow-up. After propensity matching, 1965 matched paired subjects were included for analysis. POAF was associated with an increased risk of future AF (Hazard ratio (HR) 1.40, 95%CI=1.09-1.79, p=0.008) and heart failure hospitalization (HR 1.58, 95%CI 1.23-2.04, p<0.001); however, POAF did not significantly correlate with the risk of TIA/ischemic stroke (HR 1.17, 95%CI 0.85-1.60, p=0.343). Kaplan-Meier analysis showed that POAF was a significant predictor for future AF, HF hospitalization, and overall mortality, but not for TIA/ischemic stroke. Conclusion In the Asian population, POAF after cardiac surgery increased the risk of future AF, heart failure, and overall mortality, but was not associated with future TIA/ischemic stroke.